Early testosterone replacement attenuates intracellular calcium dyshomeostasis in the heart of testosterone-deprived male rats - Weerateerangkul P. (2017)
© 2017 Elsevier Ltd Background Testosterone deficiency in elderly men increases the risk of cardiovascular disease. In bilateral orchiectomized (ORX) animals, impaired cardiac Ca 2+ regulation was observed, and this impairment could be improved by testosterone replacement, indicating the important role of testosterone in cardiac Ca 2+ regulation. However, the temporal changes of Ca 2+ dyshomeostasis in testosterone-deprived conditions are unclear. Moreover, the effects of early vs. late testosterone replacement are unknown. We hypothesized that the longer the deprivation of testosterone, the greater the impairment of cardiac Ca 2+ homeostasis, and that early testosterone replacement can effectively reduce this adverse effect. Methods Male Wistar rats were randomly divided into twelve groups, four sets of three. The first set were ORX for 2, 4 and 8 weeks, the second set were sham-operated groups of the same periods, the third set were ORX for 8 weeks coupled with a subcutaneous injection of vehicle (control), testosterone during weeks 1–8 (early replacement) or testosterone during weeks 5–8 (late replacement), and finally the 12-week sham-operated, ORX and ORX treated with testosterone groups. Cardiac Ca 2+ transients (n = 4-5/group), L-type calcium current (I Ca-L ) (n = 4/group), Ca 2+ regulatory proteins (n = 6/group) and cardiac function (n = 5/group) were determined. Results In the ORX rats, impaired cardiac Ca 2+ transients and reduced I Ca-L were observed initially 4 weeks after ORX as shown by decreased Ca 2+ transient amplitude, rising rate and maximum and average decay rates. No alteration of Ca 2+ regulatory proteins such as the L-type Ca 2+ channels, ryanodine receptor type 2, Na + -Ca 2+ exchangers and SERCA2a were observed. Early testosterone replacement markedly improved cardiac Ca 2+ transients, whereas late testosterone replacement did not. The cardiac contractility was also improved after early testosterone replacement. Conclusions Impaired cardiac Ca 2+ homeostasis is time-dependent after testosterone deprivation. Early testosterone replacement improves cardiac Ca 2+ transient regulation and contractility, suggesting the necessity of early intervention in conditions of testosterone-deprivation.